Uttarakhand Third Five-Year Plan Progress Report 1964-65 - Planning Commission (Planning Commission, 1962)
The Uttarakhand Third Five-Year Plan Progress Report for 1964-65 provides a comprehensive review of developmental initiatives across multiple sectors in the region. Key achievements include the establishment of 18 model orchards and distribution of over 161,000 fruit plants, expansion of minor irrigation projects with enhanced flood control measures, and treatment of 1,070 acres for soil conservation. Animal husbandry development included 94 stockmen centers treating more than 104,000 animals, while community development efforts focused on increasing agricultural productivity and literacy. Power projects in Uttarkashi and Pithoragarh advanced electricity supply, and cottage industries, particularly wool and herb cultivation, strengthened local economies. Infrastructure improvements encompassed 39.5 miles of new motor roads and enhancements in transport and communication. Education expanded through 50 new primary schools and support to 111 non-government junior high schools. Health initiatives included 23 maternity and child health centers, improved allopathic care, and extensive public awareness campaigns through cultural programs, exhibitions, and radio outreach. Financial allocations totaled significant investments in horticulture, irrigation, and education. The report underscores Uttarakhand’s strategic commitment to sustainable socio-economic development, integrating agricultural, health, education, and community engagement measures to uplift regional living standards.
Uttar Pradesh
Uttar Pradesh
Keywords: Uttarakhand Development; Third Five-Year Plan; Horticulture Expansion; Minor Irrigation; Flood Control; Forest Conservation; Animal Husbandry; Community Development; Power Projects; Education Infrastructure; Health Services; Public Awareness